Sequential bargaining in a new-Keynesian model with frictional unemployment and staggered wage negotiation - Gregory de Walque; Olivier Pierrard; Henri Sneessens; Raf Wouters (European Central Bank (ECB), 2009)
We consider a model with frictional unemployment and staggered wage bargaining where hours worked are negotiated every period. The workers' bargaining power in the hours negotiation affects both unemployment volatility and inflation persistence. The closer to zero this parameter, (i) the more firms adjust on the intensive margin, reducing employment volatility, (ii) the lower the effective workers' bargaining power for wages and (iii) the more important the hourly wage in the marginal cost determination. This set-up produces realistic labor market statistics together with inflation persistence. Distinguishing the probability to bargain the wage of the existing and the new jobs, we show that the intensive margin helps reduce the new entrants wage rigidity required to match observed unemployment volatility.
Keywords: E31; E32; E52; J64; 330; DSGE; monetary policy; Nominal Wage Rigidity; Search and matching; Lohnrigidität; Tarifverhandlungen; Geldpolitik; Lohnstückkosten; Dynamisches Gleichgewicht; Theorie; USA